Efficiency Enhancement of Cu2ZnSn(S, Se)4 Solar Cells via Alkali Metals Doping. Issue 7 (29th January 2016) - Hsieh, Yao‐Tsung; Han, Qifeng; Jiang, Chengyang; Song, Tze‐Bin; Chen, Huajun; Meng, Lei; Zhou, Huanping; Yang, Yang
Abstract : Doping of alkali metals in precursor solutions demonstrates an effective strategy to achieve high efficiency Cu2 ZnSn(S, Se)4 solar cells. The properties of doped films are related to alkali metal radius. Smaller alkali atoms are beneficial for increasing carrier concentration, whereas larger atoms are conducive to grain growth. Over 8% efficiency of K‐doped Cu2 ZnSn(S, Se)4 solar cell with optimized CdS thickness is realized.